2022
DOI: 10.3390/vaccines10091408
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare Workers’ Worries and Monkeypox Vaccine Advocacy during the First Month of the WHO Monkeypox Alert: Cross-Sectional Survey in Saudi Arabia

Abstract: Background: Monkeypox virus re-surged in May 2022 as a new potential global health threat, with outbreaks bursting in multiple countries across different continents. This study was conducted in Saudi Arabia during the first month following the WHO announcement of the Monkeypox outbreak, to assess healthcare workers (HCWs) perceptions of, worries concerning, and vaccine acceptance for, Monkeypox, in light of the resolving COVID-19 pandemic. Methods: A national cross-sectional survey was conducted between 27 May… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 42 publications
4
35
1
1
Order By: Relevance
“…Sallam et al [16] reported that male are more informed while Jairoun et al [24] showed that females had the highest level of knowledge. The last category (females) in association with individuals who were not infected with COVID-19 and medical students are more worried about human monkeypox as reported by Aljamaan et al [21] In this way, the level of worry varied from the different studies. This level varied from 26.37% of the total population [26] and 28.5% among Frensh and Belgian healthcare workers [27] to 60.4% among the general population in Saudi Arabia [15].…”
Section: Resultsmentioning
confidence: 89%
See 2 more Smart Citations
“…Sallam et al [16] reported that male are more informed while Jairoun et al [24] showed that females had the highest level of knowledge. The last category (females) in association with individuals who were not infected with COVID-19 and medical students are more worried about human monkeypox as reported by Aljamaan et al [21] In this way, the level of worry varied from the different studies. This level varied from 26.37% of the total population [26] and 28.5% among Frensh and Belgian healthcare workers [27] to 60.4% among the general population in Saudi Arabia [15].…”
Section: Resultsmentioning
confidence: 89%
“…This level varied from 26.37% of the total population [26] and 28.5% among Frensh and Belgian healthcare workers [27] to 60.4% among the general population in Saudi Arabia [15]. Moreover, 37.5% of the studied Saudi healthcare worker were more concerned about HMPX than COVID-19 [21].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…An online survey of HCWs and the public in KSA was conducted from May 27 to June The survey tool was adopted from our published research on COVID-19 with modifications related to the new MPD outbreak [12][13][14][15][16][17][18]. The final version was tested for content validity by our assigned research experts and piloted among ten HCWs for clarity and consistency.…”
Section: Methodsmentioning
confidence: 99%
“…This study aimed to assess the Saudi Arabian public and HCWs' knowledge about MPD and their information-seeking attitude during the first month of the WHO alert about MPD, before any cases were yet reported in the Kingdom of Saudi Arabia (KSA), as the first MPD was reported by the Ministry of Health (MOH) on July 14, 2022 [11]. The survey tool was adopted from our published research on COVID-19 with modifications related to the new MPD outbreak [12][13][14][15][16][17][18]. The final version was tested for content validity by our assigned research experts and piloted among ten HCWs for clarity and consistency.…”
Section: Introductionmentioning
confidence: 99%